2014
DOI: 10.1021/ja5080739
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective N-Heterocyclic Carbene-Catalyzed β-Hydroxylation of Enals Using Nitroarenes: An Atom Transfer Reaction That Proceeds via Single Electron Transfer

Abstract: A novel oxidative N-heterocyclic carbene-catalyzed reaction pathway has been discovered. Alkyl and aryl enals undergo β-hydroxylation via oxygen atom transfer from electron-deficient nitrobenzenes, followed by trapping of the resultant acyl azolium by the solvent. The proposed mechanism involves a single electron transfer event to initiate the reaction followed by radical recombination. This represents a profound mechanistic departure from the established two-electron disconnects in NHC catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
2
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(78 citation statements)
references
References 34 publications
4
66
2
6
Order By: Relevance
“…Interestingly, a radical species was also observed when the enal was subjected to the standard conditions but without the addition of dioxindole (Scheme 4, spectrum b), which confirms the generation of the homoenolate radical from enal in the presence of NHC and nitrobenzene. 8,17 In addition, an essentially identical EPR signal was observed for the real reaction mixture (Scheme 4, spectrum c).…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…Interestingly, a radical species was also observed when the enal was subjected to the standard conditions but without the addition of dioxindole (Scheme 4, spectrum b), which confirms the generation of the homoenolate radical from enal in the presence of NHC and nitrobenzene. 8,17 In addition, an essentially identical EPR signal was observed for the real reaction mixture (Scheme 4, spectrum c).…”
Section: Resultssupporting
confidence: 58%
“…Firstly, the addition of NHC to enals gives the corresponding Breslow intermediate I , which is partially oxidized to the radical cation intermediate II in the presence of nitrobenzene as the single electron oxidant. 8,17 In the meantime, the generated radical anion III could abstract a hydrogen from dioxindole 2 to give its enolate radical IV . The cross-coupling of the enolate radical II and the homoenolate radical IV affords adduct V , which is tautomerized to γ-hydroxy acylazolium VI .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NHC pre-catalysts with electrondeficient N-aryl substituents (4d, 4e) 13 led to no formation of 3a (entries 4-5). This result is different from Rovis's study 3 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 system triazolium-based NHCs with electron-deficient N-aryl substituents could mediate the reaction. The use of amino acidderived NHC catalyst 4f 14 afforded 3a with an improved yield but unfortunately unsatisfactory ee (entry 6).…”
Section: R'contrasting
confidence: 73%
“…It is important to note that near the completion of our study, Rovis and co-workers reported carbene-catalyzed β-hydroxylation of enals via SET processes using nitropyridine N-oxide as an oxidant. 3 In Rovis's reaction, a homoenolate radical cation intermediate was proposed; and the β-hydroxyl ester products were obtained in moderate yields and 63-92% ee. In our system, it appears a radical process involving both N-and O-centered radicals occurred.…”
mentioning
confidence: 99%